Reducing the Toxicity of Aflatoxin in Broiler Chickens' Diet by Using Probiotic and Yeast - Motawe, H.F.A.; Salam, A.F. Abdel; El Meleigy , Kh. M. (International Journal of Poultry Science, 2014)
The aim of this study was evaluating the aflatoxins (AFS) removal ability of probiotic bacteria and yeast. Two hundred and seventy one-day-old (Ross 308) broiler chicks were randomly divided into nine experimental groups. The dietary treatments were: 1 control, 4 and 5 artificially contaminated diets with 0.5 and 1 mg of AFS, respectively; 2 and 3 received control plus probiotic or yeast 1%, respectively. 6 and 7, received AFS contaminated diets (0.5 mg) plus yeast and yeast plus probiotic, respectively. The criteria of evaluation included body weight gain (BWG), feed consumption (FC) and feed conversion ratio (FCR). The toxic effect of aflatoxins were apparently in groups received AFS contaminated diet which showed significantly lower BWG and FC and impaired FCR compared with control diet. Such effects could be overcame by adding probiotic bacteria and yeast to aflatoxin treated groups. On the other hand, AFS treated group showed significant increase in liver and kidney functions. The intakes of probiotic with yeast significantly alleviated the elevation of ALT, AST, urea and creatinine levels. The results indicated the effect of probiotic plus yeast as a potential protective agent against aflatoxin toxicity which decrease the risk of occurrence of liver and kidney dysfunction.